Vizantijsko plavo . Byzantine Blue - Marinković, Dragan (VANS (Beograd), 1993)
This enigmatic artsy movie is a not very successful attempt at a screen adaptation of several different short stories by Serbian writer Milorad Pavić, internationally acclaimed author of “The Dictionary of the Khazars.” In its basics, it is a genuine if strange love story between two completely different people. She is in her twenties, a funny, playful and beautiful girl who makes hasty decisions and is a bit cynical about men. She also studies mathematics and is skilful with her computer where she stores her intimate thoughts, though this “emotional relationship” only shows her loneliness. Following a trail of blue dust the girl meets an unusual man and soon a bizarre intellectual and carnal romance develops between the two. He is older then her and always had to work hard and thus accepts that sometimes things slip from his hands, although he has talent, intelligence and hidden energy. Recently, he broke with his past and now searches obsessively for the fourth, secret element of the “Byzantine blue”, that special nuance of blue used by medieval Byzantine icon painters. It turns out at the end that he was searching for the formula of eternity.